An epidemiologic overview of acute kidney injury in intensive care units - Santos,Reginaldo Passoni dos (2019)
SUMMARY INTRODUCTION Acute kidney injury (AKI) is a frequent event among critically ill patients hospitalized in intensive care units (ICU) and represents a global public health problem, being imperative an interdisciplinary approach. OBJECTIV To investigate, through literature review, the AKI epidemiology in ICUs. METHODS: Online research in Medline, Scientific Electronic Library Online, and Latin American and Caribbean Literature in Health Sciences databases, with analysis of the most relevant 47 studies published between 2010 and 2017. RESULTS Data of the 67,033 patients from more than 300 ICUs from different regions of the world were analyzed. The overall incidence of AKI ranged from 2.5% to 92.2%, and the mortality from 5% to 80%. The length of ICU stay ranged from five to twenty-one days, and the need for renal replacement therapy from 0.8% to 59.2%. AKI patients had substantially higher mortality rates and longer hospital stays than patients without AKI. CONCLUSION AKI incidence presented high variability among the studies. One of the reasons for that were the different criteria used to define the cases. Availability of local resources, renal replacement therapy needs, serum creatinine at ICU admission, volume overload, and sepsis, among others, influence mortality rates in AKI patients.